Psychotherapy as a Moderator of the Relationship Between Coping Strategies and Anxiety During the COVID-19 Pandemic - Merlo, Gianluca; Nicastro, Lucia; Taibi, Davide (Frontiers in Psychology, 2021)
The COVID-19 pandemic has led to the development of several risk factors for mental health, not only for people directly infected but also for those experiencing social isolation, loneliness, and concern for their health. The impact of these factors on individuals’ health and wellbeing also depends on the type of coping strategies adopted. Moreover, one of the main effects of COVID-19 is the increase in the prevalence of people who manifest anxious or depressive syndromes. This study investigates the relationship between coping strategies and a multidimensional assessment of anxiety symptoms measured during the COVID-19 pandemic in people who had psychotherapy sessions at least once in their life (clinical group) and those who have never done it (not-clinical group). The results of a questionnaire administered online to Italian subjects from June to July 2020 were analyzed through multiple linear regressions methods to evaluate the role of psychotherapy as moderator between anxiety symptoms and coping strategies. The results of this study highlight that there are substantial differences in functioning between the clinical and not-clinical groups, underlying the key role of psychotherapy as a moderator between anxiety and the coping strategies of avoidance, social support, and positive attitude.